0025 School based injury prevention program offers opportunity to expand child passenger safety (CPS) efforts. (26th April 2015) - Walt, Craig; Bonsu, Patricia
Abstract : Statement of purpose: Unintentional injuries are the leading cause of death in York County in those age 5–24 years (2013 County Profiles, PA Department of Health). Risk Watch is a school-based injury prevention program aimed at reducing unintentional injuries and deaths. The York City Bureau of Health (YCBH) implements Risk Watch and engages in additional injury-prevention efforts related to Child Passenger Safety (CPS), by providing educational instruction by CPS Technicians and participating in community events. These activities aim to reduce unintentional injuries and deaths in York County. Methods/Approach: YCBH administered pre-test surveys to 70 1 st grade Risk Watch students to assess knowledge and behaviours related to safety and injury prevention and an additional CPS questionnaire. The pre-test surveys were reviewed to identify areas that the students lacked knowledge of safe behaviour and/or reported risky behaviours while the CPS questionnaires assessed the need for additional CPS services. Results: Results from the CPS questionnaire demonstrated that students, families, and caregivers engaged in risky or unsafe behaviours related to CPS. These findings recognise the need to offer additional CPS services to the students and their families. By assessing reported behaviours among students, YCBH obtained relevant data used to initiate dialogue with the school staff, families, and caregivers about the importance of CPS. The data serves to strengthen the promotion of CPS seat use and laws in the school as well as to engage families and caregivers in utilising CPS services offered by YCBH. Conclusions: Implementing a comprehensive injury prevention curriculum offers opportunities to provide targeted injury prevention programs. Risk Watch enabled YCBH to collect data, analyse findings, and provide services in an identified area of need, Child Passenger Safety. The local data reinforces CPS promotion and engages parents and caregivers. This approach effectively allocates efforts and resources to at-risk populations. Significance and contribution to the field: Comprehensive injury prevention programs can be used to effectively allocate efforts and resources by providing targeted programs in the identified areas of need to the populations most at risk. Additionally, the collection of local data is valuable in promoting injury prevention awareness and services and improves the efficacy of available programs.